Ergodic theory, dynamical systems, and the continuing influence of John C. Oxtoby - Oxtoby Centennial Conference (Bryn Mawr, PA 30-31 Oct 2010); Auslander, Joseph; Johnson, Aimee; Silva, Cesar E.; Oxtoby, John C.; Williams Ergodic Theory Conference (Williamstown, MA 27-29 July 2012); AMS Special Session, Ergodic Theory and Symbolic Dynamics (Baltimore, MD 17-18 January 2014) (Providence : American Mathematical Society, 2016)
Contains articles covering a variety of topics in measurable, symbolic and complex dynamics. It also includes a survey article on the life and work of John Oxtoby, providing a source of information about the many ways Oxtoby's work influenced mathematical thought in this and other fields.
* E. Akin, Conjugacy in the Cantor set automorphism group* S. Alpern, J. Auslander, and C. E. Silva, The mathematical work of John C. Oxtoby* T. I. Andress and E. A. Robinson Jr., The Cech cohomology and the spectrum for 1-dimensional tiling systems* K. Carroll and K. Petersen, Markov diagrams for some non-Markovian systems* D. Creutz, Contractive spaces and relatively contractive maps* R. L. Devaney, Mandelpinski structures in the parameter planes of rational maps* S. Ferenczi, J. Kulaga-Przymus, M. Lemanczyk, and C. Mauduit, Substitutions and Mobius disjointness* T. French, N. Ormes, and R. Pavlov, Subshifts with slowly growing numbers of follower sets* J. Furno, Haar measures and Hausdorff dimensions of $p$-adic Julia sets* J. Hawkins, Lebesgue measure theoretic dynamics of rational maps* A. Hill, The inverse problem for canonically bounded rank-one transformations* S. Kass and K. Madden, Higher dimensional shift spaces with shear* J. Kulaga-Przymus, M. Lemanczyk, and B. Weiss, Hereditary subshifts whose simplex of invariant measures is Poulsen* D. Ralston, Substitutions, symbolic codings, and discrepancy* B. D. Springer, Nearly continuous even Kakutani equivalence of nearly continuously rank-one transformations* K. Yancey, Dynamics of self-similar interval exchange transformations on three intervals.
Includes bibliographical references and index.
Keywords: Measure theory -- Congresses; Ergodic theory -- Congresses; Topological spaces -- Congresses